Lassa fever in pregnancy: a systematic review and meta-analysis. (3rd March 2020) - Kayem, Nzelle D; Benson, Charlotte; Aye, Christina Y L; Barker, Sarah; Tome, Mariana; Kennedy, Stephen; Ariana, Proochista; Horby, Peter
Abstract: Lassa fever is a zoonotic infection endemic to West Africa and is known to have adverse effects in pregnancy. We sought to synthesize and critically appraise currently available evidence on the effects of Lassa fever in pregnancy. An exhaustive bibliographic search from dates of inception to 30 September 2019 yielded 13 studies, from which individual patient data were extracted. The absolute risk of maternal death associated with Lassa fever was estimated at 33.73% (95% CI 22.05 to 46.42%, I 2 =72.40%, p=0.0014). The relative risk of death in pregnant women compared with non-pregnant women was estimated at 2·86 (95% CI 1.77 to 4.63, I 2 =27.27%, p=0.239). The formal gap analysis shows imprecise data on the risk of Lassa-related maternal and perinatal mortality and insufficient data for other pregnancy outcomes. The currently available evidence for the use of ribavirin in pregnant patients is not conclusive. With a threefold increased risk of mortality, there is a need to prioritize pregnant women as a special subgroup of interest for Lassa research. Robust prospective studies estimating the true incidence of adverse maternal and perinatal outcomes and randomized controlled trials to evaluate the efficacy of therapeutics for maternal Lassa virus infection are urgently needed.